2012
DOI: 10.21608/aeji.2012.15962
|View full text |Cite
|
Sign up to set email alerts
|

AIDS Effects in Liver and Biliary Tract by using Ultrasound in Sudan

Abstract: Liver enlargement and gall bladder wall thickening are common effects develop due to AIDS infection in population at Khartoum state, Sudan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
2
3
2
Order By: Relevance
“…Different hepatobiliary sonographic abnormalities such as enlarged gallbladder (GB), increased liver echogenicity, hepatomegaly, thickened GB wall, gallbladder sludge and stone were observed in this study which were comparable with those documented by other authors (Obajimi et al (2008); Igbinedion et al (2009); Pawar et al (2013); Mahmoud et al (2012). Some of these abnormal ultrasound findings (enlarged GB, increased liver echogenicity and hepatomegaly) correlated significantly with CD 4 + count (P = 0.001).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Different hepatobiliary sonographic abnormalities such as enlarged gallbladder (GB), increased liver echogenicity, hepatomegaly, thickened GB wall, gallbladder sludge and stone were observed in this study which were comparable with those documented by other authors (Obajimi et al (2008); Igbinedion et al (2009); Pawar et al (2013); Mahmoud et al (2012). Some of these abnormal ultrasound findings (enlarged GB, increased liver echogenicity and hepatomegaly) correlated significantly with CD 4 + count (P = 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is also similar to the report of the Joint United Nations Programme on HIV/AIDS (UNAID), 2010) which documented that the percentage of women living with HIV/AIDS increased from 43% in 1999 to 50% in 2010 and that Sub-Sahara African women comprised 59% of adults infected with HIV (Global Fact sheet, 2012). The sex ratio in this study was however at variance with the study documented in Sudan by Mahmoud et al (2012) which showed a higher male preponderance of 66%. The finding of female preponderance in this study could be due to the fact that females" genital anatomy places them more at risk for sexually transmitted infections, compared to men (Center for Disease Control and Prevention Fact sheet, 2017).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In line with this, Mahmoud et al . [ 6 ] and Bhabhor et al . [ 3 ] reported that males were most prone to experience the anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…3 Antiretroviral therapy’s development and widespread use have increased life expectancy and enhanced quality of life, which may be why these abdominal signs are now becoming more common. [ 6 , 7 ] It is well-recognized that HIV/AIDS can affect many organs and cause a wide range of clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%